A Study of Clinical Profile of Patients Presenting with Topical Corticosteroid Induced Facial Dermatoses - Abhineetha Hosthota; BC Chandan; Bhargavi Chitturi; Afreena Nilofer; Ankitha Ramesh; Abhishek Bharti (Perspectives In Medical Research)
Introduction: The injudicious use of Topical corticosteroid (TC) over the face has resulted in various complications, encountered day to day. Indian market is flooded with more than 18 different steroid molecules. Methodology: A hospital-based cross-sectional study was conducted on 170 patients at a tertiary care centre. A pre-structured proforma was used to collect socio-demographic details of the subjects with facial dermatoses due to TC misuse for more than 2 weeks. Results: The commonest age group affected was 20-21 years (78.2%) with mostly females (70.6%). Frequent indication for application of TC was melasma (50.0%), Acne (24.1%) and others. Subjects (40.6%) brought a combination of TCs over the counter as a suggestion from friends & relatives. Cutaneous findings of TSDF were exacerbation of pre-existing melasma (41.2%). Conclusion: The results of this study underline the need of strict laws. Futher, awareness creation among patients and primary care physicians should be given prime importance to prevent the epidemic.